Cardiometabolic risk among rural Native American adults in a large multilevel multicomponent intervention trial. - Leslie C Redmond; Michelle Estradé; Margarita S Treuth; Caroline R Wensel; Lisa Poirier; Marla Pardilla; Joel Gittelsohn (Public Library of Science (PLoS), 2023)
This cross-sectional analysis of the baseline evaluation sample of the Obesity Prevention and Evaluation of InterVention Effectiveness in Native Americans 2 (OPREVENT2) study included 601 Native American adults ages 18-75 living in rural reservation communities in the Midwest and Southwest United States. Participants completed a self-report questionnaire for individual and family history of hypertension, heart disease, diabetes and obestiy. Body mass index (BMI), percent body fat, and blood pressure were measured by trained research staff. About 60% of respondents had a BMI >30 kg/m2. Approximately 80% had a waist-to-hip ratio and percent body fat classified as high risk, and nearly 64% had a high-risk blood pressure measurement. Although a large proportion of participants reported a family history of chronic disease and had measurements that indicated elevated risk, relatively few had a self-reported diagnosis of any chronic disease. Future studies should examine potential connections between healthcare access and discordance in self-reported versus measured disease risks and diagnoses.